Inference Claims as Assertions - Mckeon, Matthew William (Informal Logic)

(untitled) (Informal Logic, 2021)
When a speaker states an argument in arguing—in its core sense—for the conclusion, the speaker asserts, as opposed to merely implies or implicates, the associated inference claim to the effect that the conclusion follows from the premises. In defense of this, I argue that how an inference claim is conveyed when stating an argument is constrained by constitutive and normative conditions for core cases of the speech of arguing for a conclusion. The speech act of assertion better reflects such conditions than does implication, conversational implicature, or conventional implicature.